Development as Labour and Labour as Development: Korczak’s Philosophy of Labour Against the Background of Interwar Childhoods - Rakoczy , Marta (Studia Historiae Oeconomicae, 2023)
In this article, I consider two Korczakian conceptions complementary to each other of children’s labour as a means of building their agency and autonomy. The first is the concept of labour as development. While the second is development as labour. I analyse testimonies from Korczak’s institutions, including notes gleaned from children’s accounts Wspomnienia z maleńkości dzieci Naszego Domu w Pruszkowie [Recollections from the Children of Our Home in Pruszków], children’s texts (Mały Przegląd [Little Review]) and programme and literary texts by Janusz Korczak/Henryk Goldszmit and Maria (Maryna) Falska, who collaborated with him. In the anthropological perspective of new childhood studies I ponder the radicalism of Korczak’s projects involving child labour in light of the time, their perspective on child labour, and childhood itself. In what sense did they have modern origins? And in what sense did they transcend modernity – along with its concepts of childhood and child development?